Implementasi Metode Kano Dalam Menganalisis Kepuasan Pasien Pada Klinik Pratama Dehasen Berbasis Website - Irawansa, Doni; Kanedi, Indra; Lianda, Deri (Jurnal Media Infotama, 2025)
Patient satisfaction in healthcare services is very important to pay attention to because it can provide an overview of service quality. Patients will feel satisfied if the healthcare services they receive meet or exceed their expectations, and conversely, patient dissatisfaction or disappointment will arise if the healthcare services they receive do not meet their expectations. KANO is one of the methods used to assess patient satisfaction with service quality and measure service quality by identifying patient preferences and categorizing service attributes. Thus, patient satisfaction is the level of feeling patients experience as a result of the healthcare services they receive after comparing them with their expectations. The system implementation uses PHP programming language, and the method employed in this study is System Development Life Cycle method. From the results of the testing conducted, it can be concluded that patient satisfaction using this method can be achieved effectively and establish high-quality service standards